Process optimization and evaluation of nutritional, chemical and functional properties of isolated proteins from microwave vacuum-stabilized rice bran - Rallos, Nikki Rae N.; Villarino, Casiana Blanca J. (Quezon City College of Home Economics, university of the Philippines Diliman, 2023)
The study aimed to optimize the isolation parameters of rice bran protein isolates (RBPI) from microwave-vacuum (MV) stabilized rice bran, and evaluate various properties of the optimal sample. Optimization was based on maximizing isolation time while maintaining protein isolate quality using central composite face-centered design response surface methodology (RSM). Statistical models were used to predict the effects of pH, isolation temperature (ºC), and isolation time (min), on the % yield and % purity of the protein isolates. Verification experiments were performed to validate the accuracy of the predictive models. The linear mixture model indicated that % yield was significantly (p < 0.05) affected by the isolation parameters. The parameter combination used for the optimal solution were pH 7.38, 43.83 ºC isolation temperature, and 180 min isolation time. Verification experiments concluded that only the % yield predictive model was validated. The optimal RBPI composition (dry matter basis) contains ash 4.88%, crude protein 53.29%, and fat 34.71%. In addition, the molecular weight (MW) bands were determined to be within the albumin range, which may potentially have contributed to the good functional properties (water and fat absorption capacity, gelation ability, and emulsion activity and stability) of the optimal RBPI.
Thesis (Bachelor of Science in Food Technology) -- University of the PHilippines Diliman
Includes bibliographical references (pages 45-52)
Keywords: Rice bran; Rice products